Yesterday - Today - Tomorrow: magnifying the historic space of Kuala Kedah Fort - Dziyauddin, Nor Najwa (2018)
The heritage site can be simply defined as an interesting place where people describe themselves in term of belonging to a specific place. For this study, it will reminiscence the historical values and the nostalgia of Kuala Kedah Fort area towards authentic place by enhancing the local physical character. The physical character will emphasize on the function of public space, the systematic linkages between natural area and historical area. The methodology of this study involves the implementation stage of secondary data from the government department and existing data from previous researchers which already published. The primary data has been identified the potential area to develop and preserved. Based on the strategy and design ideas inspired from the concept of ‘Reminiscence’ that has been transformed into the physical form in designing the public space to be more functional, systematic linkages and conservation of historical features to make the place be more authentic with own true local identity in facing the modernism in 2035. The aim and objectives are to bring back the unique experience and the originality monuments and buildings as well with history of Kedah’s Royalty and Colonials within the Coastal Port Town at Kuala Kedah Fort. To optimize the link of natural area and historical area that can promote the activities using a living heritage approach and lastly, to provide master plan that encourage user to experience the liveable public space that have various activities. Hopefully, this project can be used as a design strategy and guidelines for stakeholders in reviving the heritage site to give a sense of place that creates a different feeling and memorable experience.